Management of Complex Ovarian Cysts in Newborns - Our Experience - Manjiri S; Padmalatha SK; Shetty J (EL-Med-Pub, 2016)
Aims: To analyse the clinical presentation, clinicopathological correlation and management of complex ovarian cysts in newborn and infants. Materials and Methods: Over a period of 6 years (2009-2015), 25 newborns who were diagnosed to have ovarian cyst on antenatal ultrasound, were followed up. We collected data in the form of clinical features, radiological findings, pathology and mode of treatment. Results: Of the 25 fetuses who were diagnosed to have ovarian cysts, fourteen (56%) underwent spontaneous regression by 6-8 months. Eight were operated in newborn period while 3 were operated in early infancy. Seven had ovarian cyst on right side, 4 had on left side. Eight babies underwent laparoscopy while 3 underwent laparotomy. Histopathology showed varied features of hemorrhagic cyst with necrosis and calcification, serous cystadenoma with hemorrhage, benign serous cyst with hemorrhage and simple serous cyst. Post-operative recovery was uneventful in all. Conclusion: All the ovarian cysts detected antenatally in female fetuses need close follow-up after birth. Since spontaneous regression is known, only complex or larger cysts need surgical intervention, preferably by laparoscopy. Majority of the complex cysts show atrophic ovarian tissue hence end up in oophorectomy but simple cysts can be removed preserving normal ovarian tissue whenever possible.